Strategi Penegakan Hukum terhadap Jaringan Negara Islam Indonesia (NII) di Indonesia - Elidar Sari; Al Chaidar; Arif Rahman; Muammar; Tri Widya Kurniasari (JURNAL ILMIAH GEMA PERENCANA, 2025)
The persistent and unique threat posed by the Negara Islam Indonesia (NII) network, characterized by its long-term strategy of societal infiltration and the establishment of a parallel state, demands specific and adaptive law enforcement strategies. This article, which adopts a qualitative descriptive-analytical research method, examines the various legal and operational approaches employed by Indonesian law enforcement agencies in countering the NII. The analysis focuses on the application of existing laws, including anti-terrorism legislation and other relevant criminal codes, to address the NII’s distinct activities that often fall outside the conventional understanding of terrorism. The paper also investigates the intelligence-gathering techniques, surveillance methods, and arrest procedures utilized to target NII cells and leadership, considering the challenges posed by the network’s decentralized and clandestine nature. Furthermore, it evaluates the effectiveness and legality of these law enforcement strategies, exploring issues related to due process, human rights, and the potential for overreach. By analyzing specific cases and broader trends, this research aims to provide a critical assessment of the current law enforcement response to the NII in Indonesia, highlighting both successes and areas for improvement in addressing this complex and enduring security challenge.